Composite gas-sensitive material, nitrogen dioxide gas-sensitive sensor and preparation method of nitrogen dioxide gas-sensitive sensor

By using a composite gas-sensitive material of tungsten disulfide and tin dioxide, the formation of p-n heterojunctions improves conductivity and response speed, the problem of high working temperature of existing NO2 gas-sensitive materials is solved, and the detection of high sensitivity of NO2 at room temperature is achieved.

CN119660803APending Publication Date: 2025-03-21SOUTHERN POWER GRID DIGITAL GRID RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510077043.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The working temperature of existing NO2 gas-sensitive materials is high and require high temperature excitation, which limits their practical application.

Method used

A composite gas-sensitive material of tungsten disulfide and tin dioxide with a mass ratio of 1: (0.06~0.65) is used to form a p-n heterojunction by loading the tin dioxide particles on the surface of tungsten disulfide nanosheets to improve the conductivity and response speed of the material.

Benefits of technology

A good response to NO2 at room temperature is achieved, the detection limit is reduced, and the sensitivity and selectivity to NO2 are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660803A_ABST
    Figure CN119660803A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of NO2 gas detection, in particular to a composite gas-sensitive material, a nitrogen dioxide gas-sensitive sensor and a preparation method of the nitrogen dioxide gas-sensitive sensor. The chemical components of the composite gas sensitive material comprise tungsten disulfide and tin dioxide in a mass ratio of 1: (0.06-0.65), the tungsten disulfide comprises tungsten disulfide nanosheets, the tin dioxide comprises tin dioxide particles, and at least part of the tin dioxide particles are loaded on the surfaces of the tungsten disulfide nanosheets. The composite gas-sensitive material provided by the invention has low detection limit on NO2, and can realize good response to NO2 at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application involves NO 2 The technical field of gas detection specifically relates to a composite gas-sensitive material, a nitrogen dioxide gas-sensitive sensor and a preparation method thereof. Background Art

[0002] Nitrogen dioxide (NO 2 ) is a common pollutant. Excessive NO 2 Will have adverse effects on human health and the ecosystem. NO 2 The damage to health is mainly reflected in respiratory damage. Inhalation of NO 2 The gas can cause upper respiratory tract irritation symptoms, such as throat discomfort and dry cough, etc. in mild cases; in severe cases, it can cause chest tightness and cough. The adverse effects of nitrogen dioxide on the ecosystem are mainly reflected in the formation of acid rain, which can lead to reduced atmospheric visibility, acidification and eutrophication of surface water, etc. Therefore, the detection of nitrogen dioxide gas is of great significance.

[0003] Currently, NO 2 Gas-sensitive materials are mainly metal oxide semiconductor materials, which have the advantages of low cost, simple preparation method and high sensitivity. 2 The working temperature of the gas-sensitive material is relatively high. During the detection process, the gas-sensitive material needs to be excited to a high temperature of 250°C~450°C to detect NO 2 It is not conducive to practical application. Summary of the invention

[0004] Based on this, the present application provides a composite gas-sensitive material and a preparation method thereof, a nitrogen dioxide gas-sensitive sensor and a preparation method thereof. The composite gas-sensitive material provided in the present application is sensitive to NO 2 The detection limit of NO is low and can be achieved at room temperature 2 Good response.

[0005] In a first aspect of the present application, a composite gas-sensitive material is provided, wherein the chemical components of the composite gas-sensitive material include tungsten disulfide and tin dioxide in a mass ratio of 1: (0.06-0.65),

[0006] Wherein, the tungsten disulfide comprises tungsten disulfide nanosheets, the tin dioxide comprises tin dioxide particles, and at least part of the tin dioxide particles are loaded on the surface of the tungsten disulfide nanosheets. In one embodiment, the composite gas-sensitive material has one or more of the following characteristics:

[0007] (1) The average size of the tungsten disulfide nanosheets is 100nm~300nm;

[0008] (2) The molar ratio of the tungsten disulfide to the tin dioxide is 1:(0.1~1).

[0009] The second aspect of the present application provides a method for preparing the composite gas-sensitive material according to any one of the embodiments of the first aspect of the present application, comprising the following steps:

[0010] Dispersing the tungsten disulfide nanosheets in a first solvent to prepare a tungsten disulfide dispersion;

[0011] Dispersing the tin dioxide particles in a second solvent to prepare a tin dioxide dispersion;

[0012] Under stirring conditions, the tin dioxide dispersion is added to the tungsten disulfide dispersion in batches, and after mixing, at least a portion of the tin dioxide particles are loaded on the surface of the tungsten disulfide nanosheets to prepare an intermediate dispersion;

[0013] The intermediate dispersion is subjected to solid-liquid separation, and the solid is collected to prepare the composite gas-sensitive material.

[0014] In one embodiment, the preparation method has one or more of the following characteristics:

[0015] (1) In the tungsten disulfide dispersion, the mass volume concentration of the tungsten disulfide nanosheets is 1 mg / mL to 3 mg / mL;

[0016] (2) In the tin dioxide dispersion, the mass volume concentration of the tin dioxide particles is 0.5 mg / mL to 5 mg / mL;

[0017] (3) The molar ratio of the tungsten disulfide nanosheets to the tin dioxide particles in the intermediate dispersion is 1: (0.1-1);

[0018] (4) the first solvent includes one or more of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone;

[0019] (5) The second solvent includes one or more of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone.

[0020] In one embodiment, the steps of preparing the tungsten disulfide nanosheets include:

[0021] Grinding the tungsten disulfide crystals in the presence of grinding media, and preparing an intermediate powder after drying;

[0022] Ultrasonic dispersion of the intermediate powder in a first dispersant, performing a first centrifugal treatment, collecting the supernatant, and preparing a tungsten disulfide nanosheet solution;

[0023] The tungsten disulfide nanosheet solution is subjected to a second centrifugal treatment to collect the solid phase to prepare the tungsten disulfide nanosheet;

[0024] Wherein, the process parameters of the first centrifugal treatment include: a rotation speed of 1000rpm~3000rpm;

[0025] The process parameters of the second centrifugal treatment include: a rotation speed of 7000 rpm to 9000 rpm.

[0026] In one embodiment, the preparation steps of the tungsten disulfide nanosheets have one or more of the following characteristics:

[0027] (1) The grinding medium includes one or more of acetonitrile, isopropanol and N-methylpyrrolidone;

[0028] (2) the first dispersant includes one or more of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone;

[0029] (3) In the step of ultrasonically dispersing the intermediate powder in the first dispersant, the mass volume ratio of the intermediate powder to the first dispersant is (400-600) mg: (200-400) mL;

[0030] (4) In the step of ultrasonically dispersing the intermediate powder in the first dispersant, the process parameters of the ultrasonic dispersion include: ultrasonic crushing at a power of 300W to 600W.

[0031] In one embodiment, the steps of preparing the tin dioxide particles include:

[0032] Dispersing the tin source in the second dispersant, adding a pH adjuster to adjust the pH to 3-3.5, and preparing a gel-containing dispersion;

[0033] The gel in the gel-containing dispersion is collected, dried, and then sintered to prepare the tin dioxide particles.

[0034] In one embodiment, the steps for preparing the tin dioxide particles have one or more of the following characteristics:

[0035] (1) The tin source includes tin tetrachloride pentahydrate;

[0036] (2) the second dispersant includes one or more of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone;

[0037] (3) The pH adjuster includes one or more of ammonia water, sodium hydroxide solution and potassium hydroxide solution;

[0038] (4) in the step of dispersing the tin source in the second dispersant, the mass volume ratio of the tin source to the second dispersant is (2-5) g: (5-20) mL;

[0039] (5) The process parameters of the sintering treatment include: the sintering temperature is 400℃~600℃.

[0040] The third aspect of the present application provides a nitrogen dioxide gas sensor, comprising a substrate, interdigitated electrodes and a gas sensitive layer, wherein the interdigitated electrodes are arranged on at least one side surface of the substrate, the gas sensitive layer is arranged on a side surface of the interdigitated electrodes away from the substrate, and the gas sensitive layer comprises the composite gas sensitive material described in any embodiment of the first aspect of the present application.

[0041] In one embodiment, the material of the interdigital electrodes is gold.

[0042] In a fourth aspect of the present application, a method for preparing the nitrogen dioxide gas sensor according to the third aspect of the present application is provided, comprising the following steps:

[0043] The interdigital electrodes are arranged on at least one side surface of the substrate;

[0044] The composite gas-sensitive material is made into a gas-sensitive layer coating liquid; the gas-sensitive layer coating liquid is coated on the surface of the interdigital electrode on one side away from the substrate, and after drying, the gas-sensitive layer is prepared.

[0045] The composite gas-sensitive material provided by the present application has at least the following beneficial effects:

[0046] In the composite gas-sensitive material provided in the present application, tungsten disulfide nanosheets are selected as carriers, which have a high specific surface area and can provide more active sites for loading tin dioxide particles. In addition, tin disulfide particles are used as a carrier, which can enrich NO 2 site of action.

[0047] Furthermore, tungsten disulfide nanosheets are p-type semiconductors, and tin dioxide particles are n-type semiconductors. When tin dioxide particles are loaded on the surface of tungsten disulfide nanosheets, a pn heterojunction is formed. This is conducive to improving the conductivity of the composite material, allowing electrons to be quickly transmitted in the composite material, and accelerating the gas-sensitive material to NO 2 In addition, the synergistic effect of tungsten disulfide and tin dioxide in a specific mass ratio enables the composite gas-sensitive material of the present application to respond to NO at room temperature. 2 Achieve good response and help improve the composite gas-sensitive material to NO 2 sensitivity.

[0048] In summary, the composite gas-sensitive material provided in this application is effective for NO 2The detection limit of NO is low and can be achieved at room temperature. 2 Good response to NO 2 Has good selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The composite gas-sensitive material in an example provided in this application is sensitive to NO 2 Schematic diagram of the response principle;

[0050] Figure 2 This is a SEM image of the composite gas-sensitive material prepared in Example 2 of the present application;

[0051] Figure 3 This is a TEM image of the composite gas-sensitive material prepared in Example 2 of the present application;

[0052] Figure 4 XRD diagrams of tungsten disulfide nanosheets and composite gas-sensitive materials prepared in Example 2 of the present application, as well as XRD standard cards of tin dioxide and tungsten disulfide;

[0053] Figure 5 The gas sensors prepared in Examples 1 to 4 of the present application reacted to NO with a concentration of 10 ppm at room temperature. 2 Response curve diagram of

[0054] Figure 6 The gas sensor prepared in Comparative Example 2 of the present application is sensitive to NO at a concentration of 10 ppm at room temperature. 2 Response curve diagram of

[0055] Figure 7 The gas sensor of Example 2 of the present application is responsive to 1ppm, 2.5ppm, 5ppm, 10ppm, 25ppm, 50ppm and 100ppm of NO at room temperature. 2 Continuous response curve diagram of

[0056] Figure 8 The gas sensor of Example 2 of the present application is subjected to 10 ppm NO every 3 days at room temperature. 2 A bar graph of the response values ​​for a test;

[0057] Fig. 9 The gas sensor of Example 2 was exposed to 10 ppm NO at room temperature. 2 , CO 2 NH 3 , H 2 S and H 2 A histogram of the response values ​​in . DETAILED DESCRIPTION

[0058] The following is a further complete and clear description of the composite gas-sensitive material, nitrogen dioxide gas-sensitive sensor and preparation method of the present application in conjunction with specific examples. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0059] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0060] As used herein, "one or more" refers to any one, any two, or any two or more of the listed items.

[0061] In this application, "first aspect", "second aspect", "third aspect", "fourth aspect", "fifth aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", "fifth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0062] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0063] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0064] The percentage contents involved in this application, unless otherwise specified, refer to mass percentage for solid-liquid mixing and solid-solid mixing, and refer to volume percentage for liquid-liquid mixing.

[0065] The percentage concentrations mentioned in this application, unless otherwise specified, refer to the final concentration, which refers to the percentage of the added component in the system after the addition of the component.

[0066] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.

[0067] In a first aspect of the present application, a composite gas-sensitive material is provided, wherein the chemical components of the composite gas-sensitive material include tungsten disulfide and tin dioxide in a mass ratio of 1: (0.06-0.65),

[0068] The tungsten disulfide includes tungsten disulfide nanosheets, the tin dioxide includes tin dioxide particles, and at least part of the tin dioxide particles are loaded on the surface of the tungsten disulfide nanosheets.

[0069] Tungsten disulfide is a two-dimensional transition metal chalcogenide with high carrier mobility and excellent environmentally friendly properties. However, when single tungsten disulfide is used as a gas-sensitive material, it has the disadvantage of low sensitivity. Based on this, the present application selects tungsten disulfide nanosheets with a higher specific surface area as a carrier, which can provide more active sites for loading tin dioxide particles. At the same time, tin disulfide particles as a carrier can enrich NO with its higher specific surface area. 2 site of action.

[0070] Furthermore, the tungsten disulfide nanosheets are p-type semiconductors, and the tin dioxide particles are n-type semiconductors. When the tin dioxide particles are loaded on the surface of the tungsten disulfide nanosheets, a pn heterojunction is formed. Specifically, the composite gas-sensitive material provided in the present application is sensitive to NO 2 The schematic diagram of the response is as follows: Figure 1 When the composite gas-sensitive material provided by the present application is exposed to NO 2 In the gas environment, NO 2 The gas captures electrons from the tin dioxide particles, forming NO 2 — This will cause the balance of the built-in electric field at the pn junction to be destroyed, and the excess holes will return to the tungsten disulfide nanosheets, thus forming a new equilibrium state. In this equilibrium state, the width of the potential barrier at the interface is reduced, increasing the conductivity of the composite gas-sensitive material. And because tungsten disulfide is hole conductive, more holes will further increase the conductivity of tungsten disulfide, improving the resistance to NO 2 In addition, the synergistic effect of the specific mass ratio of tungsten disulfide and tin dioxide also avoids the large-scale agglomeration of tin dioxide nanoparticles and tungsten disulfide nanosheets, increases the specific surface area and the number of active sites, and thus enhances the gas sensing performance.

[0071] In addition, the composite gas-sensitive material of the present application can react with NO at room temperature. 2 Achieve good response and help improve the composite gas-sensitive material to NO 2sensitivity.

[0072] In summary, the composite gas-sensitive material provided in this application is effective for NO 2 The detection limit of NO is low and can be achieved at room temperature. 2 Good response to NO 2 Has excellent selectivity.

[0073] It can be understood that the mass ratio of the tungsten disulfide to the tin dioxide can be selected from any value between 1: (0.06~0.65). For example, the mass ratio of the tungsten disulfide to the tin dioxide includes but is not limited to 1: 0.06, 1: 0.1, 1: 0.2, 1: 0.3, 1: 0.4, 1: 0.5, 1: 0.6, 1: 0.61, 1: 0.62 or 1: 0.65, or within the range of any two of the above point values.

[0074] The appropriate mass ratio of tungsten disulfide and tin dioxide helps to form a composite structure with stable performance. At this time, the tin dioxide particles can be evenly loaded on the surface of the tungsten disulfide nanosheets, avoiding excessive accumulation or uneven distribution of tin dioxide particles, thereby avoiding the decrease in gas diffusion and transmission caused by excessive accumulation, and the NO caused by uneven distribution. 2 Insufficient reactive sites in the molecule. 2 During the response process, the resistance change of the composite gas-sensitive material is the detection of NO 2 The present application specifies the mass ratio of tungsten disulfide nanosheets and tin dioxide particles to ensure that the conductivity of the gas-sensitive material is moderate, so as to facilitate the rapid transmission of electronic signals and ensure the response speed of the gas-sensitive material; at the same time, it can avoid the reduction of the intrinsic resistance of the gas-sensitive material caused by the excessive conductivity of the composite gas-sensitive material, that is, the composite gas-sensitive material adsorbs NO 2 After the molecules are separated, the resistance change caused is not easy to be detected, which leads to a decrease in sensitivity.

[0075] In one example, the average size of the tungsten disulfide nanosheets is 100nm~300nm.

[0076] In the present application, "size" refers to the long diameter of the nanosheet plane. Among them, "long diameter" means the length in the direction of the maximum length on the nanosheet plane. In the present application, the average size of the tungsten disulfide nanosheets is limited. On the one hand, it can avoid excessive scattering and obstruction of carriers during transmission caused by the low size of tungsten disulfide, thereby ensuring a certain transmission efficiency. On the other hand, the size of the tungsten disulfide nanosheets is not too large, which enables the carriers to quickly respond to the adsorption and desorption process of the gas within a relatively short distance, thereby improving the response speed and sensitivity of the gas-sensitive material.

[0077] In one example, at least some of the tin dioxide particles aggregate to form aggregates. It is understandable that there are certain interaction forces between the tin dioxide particles, such as van der Waals forces, which cause the tin dioxide particles to aggregate together. At this time, the aggregates are supported on the surface of the tungsten disulfide nanosheets.

[0078] In one example, the molar ratio of the tungsten disulfide nanosheets to the tin dioxide particles is 1:(0.1-1). For example, the molar ratio of the tungsten disulfide nanosheets to the tin dioxide particles includes but is not limited to 1:0.1, 1:0.2, 1:0.28, 1:0.29, 1:0.3, 1:0.32, 1:0.35, 1:0.4, 1:0.48, 1:0.5, 1:0.55, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1, or within the range of any two of the above point values.

[0079] In a second aspect of the present application, there is provided a method for preparing the composite gas-sensitive material as described in any example of the first aspect of the present application, comprising the following steps:

[0080] S10, dispersing the tungsten disulfide nanosheets in a first solvent to prepare a tungsten disulfide dispersion;

[0081] S20, dispersing the tin dioxide particles in a second solvent to prepare a tin dioxide dispersion;

[0082] S30, adding the tin dioxide dispersion to the tungsten disulfide dispersion in batches under stirring conditions, and after mixing, allowing at least a portion of the tin dioxide particles to be loaded on the surface of the tungsten disulfide nanosheets to prepare an intermediate dispersion;

[0083] S40, performing solid-liquid separation on the intermediate dispersion, collecting the solid, and preparing the composite gas-sensitive material.

[0084] In the preparation method provided in the present application, the tungsten disulfide nanosheets and the tin dioxide particles are first dispersed separately, and then the tin dioxide dispersion is added in batches, which is conducive to controlling the loading amount and loading uniformity of the tin dioxide particles on the surface of the tungsten disulfide nanosheets. The above preparation method is simple, efficient, and has high repeatability. For example, in step S30, the method of adding in batches includes but is not limited to dripping.

[0085] In order to enable the tungsten disulfide nanosheets to maintain a good dispersion state in the first solvent, the agglomeration of the nanosheets caused by excessive concentration is avoided. In one example, in step S10, in the tungsten disulfide dispersion, the mass volume concentration of the tungsten disulfide nanosheets is 1 mg / mL~3 mg / mL. For example, in the tungsten disulfide dispersion, the mass volume concentration of the tungsten disulfide nanosheets includes but is not limited to 1 mg / mL, 1.2 mg / mL, 1.5 mg / mL, 1.8 mg / mL, 1.9 mg / mL, 2 mg / mL, 2.1 mg / mL, 2.3 mg / mL, 2.5 mg / mL, 2.8 mg / mL, or 3 mg / mL, or within the range of any two of the above point values.

[0086] In one example, in step S10, the first solvent includes one or more of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone.

[0087] In one example, in step S20, in the tin dioxide dispersion, the mass volume concentration of the tin dioxide particles is 0.5 mg / mL to 5 mg / mL. For example, in the tin dioxide dispersion, the mass volume concentration of the tin dioxide particles includes but is not limited to 0.5 mg / mL, 0.6 mg / mL, 0.8 mg / mL, 0.9 mg / mL, 1 mg / mL, 1.5 mg / mL, 1.8 mg / mL, 2 mg / mL, 2.1 mg / mL, 2.3 mg / mL, 2.5 mg / mL, 2.8 mg / mL, 3 mg / mL, 4 mg / mL or 5 mg / mL, or within the range of any two of the above point values.

[0088] In one example, in step S20, the second solvent includes one or more of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone.

[0089] In one example, in step S30, the molar ratio of the tungsten disulfide nanosheets to the tin dioxide particles in the intermediate dispersion is 1:(0.1-1).

[0090] For example, in step S10, the method of dispersing the tungsten disulfide nanosheets in the first solvent includes but is not limited to ultrasound. In step S20, the method of dispersing the tin dioxide particles in the second solvent includes but is not limited to ultrasound. In step S30, the method of mixing includes but is not limited to ultrasound. In step S40, the method of solid-liquid separation includes one or more of centrifugation, washing and drying.

[0091] In one example, the steps of preparing the tungsten disulfide nanosheets include:

[0092] a1. Grind the tungsten disulfide crystals in the presence of grinding media, and prepare intermediate powder after drying;

[0093] a2. Ultrasonic dispersion of the intermediate powder in a first dispersant, performing a first centrifugal treatment, collecting the supernatant, and preparing a tungsten disulfide nanosheet solution;

[0094] a3. Perform a second centrifugation on the tungsten disulfide nanosheet solution to collect the solid phase to prepare the tungsten disulfide nanosheet.

[0095] Ball milling of tungsten disulfide crystals under grinding media can increase friction, break and refine the crystals, and thus help increase the specific surface area. The intermediate powder is further ultrasonically dispersed, and the cavitation effect generated by ultrasonic vibration can break the agglomeration between the powders, so that the nanosheets are dispersed in the first dispersant. After two further centrifugal treatments, the first centrifugal treatment can remove larger particles and screen out nanosheets; the second centrifugal treatment can further remove impurities to avoid interference from impurities.

[0096] In one example, in step a1, the grinding medium includes one or more of acetonitrile, isopropanol and N-methylpyrrolidone. Further, in step a1, the grinding treatment time is 1h to 4h. For example, the grinding treatment time includes but is not limited to 1h, 2h, 3h or 4h, or a range formed by any two of the above point values.

[0097] In one example, in step a1, the drying process parameters include: drying temperature is 50°C to 70°C. Further, in step a1, the drying process parameters also include: drying time is 10h to 20h. For example, the drying temperature includes but is not limited to 50°C, 55°C, 58°C, 60°C, 65°C or 70°C. The drying time includes but is not limited to 10h, 12h, 14h, 16h, 18h or 20h.

[0098] In one example, in step a2, in the step of ultrasonically dispersing the intermediate powder in the first dispersant, the mass volume ratio of the intermediate powder to the first dispersant is (400-600) mg: (200-400) mL. For example, the mass volume ratio of the intermediate powder to the first dispersant includes but is not limited to 400 mg: 200 mL, 400 mg: 250 mL, 400 mg: 300 mL, 400 mg: 350 mL, 400 mg: 400 mL, 500 mg: 200 mL, 500 mg: 250 mL, 500 mg: 300 mL, 500 mg: 350 mL, 500 mg: 400 mL, 600 mg: 200 mL, 600 mg: 250 mL, 600 mg: 300 mL, 600 mg: 350 mL or 600 mg: 400 mL, or within the range of any two of the above point values.

[0099] In one example, in step a2, in the step of ultrasonically dispersing the intermediate powder in the first dispersant, the process parameters of the ultrasonic dispersion include: ultrasonic crushing at a power of 300W to 600W. Further, the time for ultrasonic crushing is 1h to 4h. By way of example, the power for ultrasonic dispersion includes but is not limited to 300W, 350 W, 400 W, 450 W, 500 W or 600 W. The time for ultrasonic crushing includes but is not limited to 1h, 1.5h, 1.8h, 2h, 2.2h, 2.5h, 2.8h or 3h.

[0100] The mass volume ratio of the intermediate powder and the first dispersant and the process parameters of ultrasonic dispersion are limited; the liquid phase exfoliation method can be used to effectively exfoliate the tungsten disulfide crystals into nanosheets to ensure the exfoliation efficiency and the stability of the nanosheets.

[0101] In one example, in step a2, the first dispersant includes one or more of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone.

[0102] Further, in step a2, the first dispersant includes an ethanol / deionized water mixed solvent. For example, the volume fraction of ethanol in the ethanol / deionized water mixed solvent is 30% to 40%.

[0103] In one example, in step a2, the process parameters of the first centrifugal treatment include: a rotation speed of 1000 rpm to 3000 rpm. Further, the process parameters for the first centrifugal treatment also include: a time of 20 min to 40 min. By way of example, the rotation speed of the first centrifugal treatment includes but is not limited to 1000 rpm, 1500 rpm, 1800 rpm, 2000 rpm, 2200 rpm, 2500 rpm, 2800 rpm or 3000 rpm.

[0104] Appropriate process parameters for the first centrifugal treatment can achieve good separation of nanosheets and unpeeled crystals under the action of centrifugal force, so that tungsten disulfide nanosheets are dispersed in the supernatant and unpeeled tungsten disulfide crystals are retained in the solid phase. If the centrifugal speed is too low, the nanosheets and crystals may not be completely separated; while if the centrifugal speed is too high, the nanosheets may be damaged or agglomerated.

[0105] In one example, in step a3, the process parameters of the second centrifugal treatment include: a rotation speed of 7000 rpm to 9000 rpm. Further, the process parameters for the second centrifugal treatment also include: a time of 20 min to 40 min. By way of example, the rotation speed of the second centrifugal treatment includes but is not limited to 7000 rpm, 7500 rpm, 7800 rpm, 8000 rpm, 8200 rpm, 8500 rpm, 8800 rpm or 9000 rpm.

[0106] Appropriate process parameters of the second centrifugal treatment can achieve good separation of nanosheets and impurities under the action of centrifugal force, so that tungsten disulfide nanosheets are dispersed in the solid phase and other impurities are retained in the supernatant.

[0107] In one specific example, the steps of preparing the tungsten disulfide nanosheets include:

[0108] (1) In the presence of a grinding medium, the tungsten disulfide crystal is ground for 1 h to 4 h, and then dried at 50 ° C to 70 ° C for 10 h to 20 h to prepare an intermediate powder.

[0109] (2) Ultrasonic dispersion of the intermediate powder in a first dispersant, performing a first centrifugal treatment at a speed of 1000 rpm to 3000 rpm for 20 min to 40 min, collecting the supernatant, and preparing a tungsten disulfide nanosheet solution, wherein the mass volume ratio of the intermediate powder to the first dispersant is (400 to 600) mg: (200 to 400) mL; the process parameters of ultrasonic dispersion include: ultrasonic crushing for 1 h to 4 h at a power of 300 W to 600 W.

[0110] (3) The tungsten disulfide nanosheet solution is subjected to a second centrifugal treatment at a rotation speed of 7000 rpm to 9000 rpm for 20 min to 40 min, and the solid phase is collected to prepare the tungsten disulfide nanosheet.

[0111] In one example, the steps of preparing the tin dioxide particles include:

[0112] b1. dispersing the tin source in the second dispersant, adding a pH adjuster to adjust the pH to 3-3.5, and preparing a gel-containing dispersion;

[0113] b2. Collecting the gel in the gel-containing dispersion, drying it, and then sintering it to prepare the tin dioxide particles.

[0114] Tin sources such as tin tetrachloride pentahydrate (SnCl 4 •5H 2 O) is dispersed in the second dispersant. At this time, tin ions (Sn 4+ ). 4+ First, a hydrolysis reaction occurs to form hydroxytin compounds. A pH adjuster is further added to adjust the pH to 3 to 3.5. Within this range, the hydroxytin compounds are gradually connected together through chemical bonds or physical interactions to form a three-dimensional network structure, thereby leading to the formation of a gel. After the gel is further sintered, the hydroxytin compounds in the gel can be converted into tin dioxide particles.

[0115] In one example, in step b1, the tin source includes tin tetrachloride pentahydrate.

[0116] In one example, in step b1, the second dispersant includes one or more of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone.

[0117] In one example, in step b1, the pH adjuster includes one or more of ammonia water, sodium hydroxide solution and potassium hydroxide solution.

[0118] In one example, in step b1, in the step of dispersing the tin source in the second dispersant, the mass volume ratio of the tin source to the second dispersant is (2-5) g: (5-20) mL. For example, the mass volume ratio of the tin source to the second dispersant includes but is not limited to 2g: 5mL, 3g: 6mL, 3.5g: 7mL, 3.5g: 7.5mL, 3.5g: 8mL, 3.5g: 8.5mL, 3.5g: 10mL, 3.5g: 15mL, 3.5g: 20mL, 4g: 8mL, 5g: 8mL, 5g: 10mL, 5g: 15mL, or 5g: 20mL, or within the range of any two of the above point values.

[0119] In one example, in step b2, after the step of collecting the gel in the gel-containing dispersion, the step further includes:

[0120] The step of washing the gel at 50°C to 70°C under water bath conditions. At 50°C to 70°C, the structure of the gel is relatively stable and the overall structure of the gel will not be destroyed. For example, under water bath conditions, the temperature for washing the gel includes but is not limited to 50°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C or 70°C. Further, after the step of washing the gel at 50°C to 70°C under water bath conditions, the step of washing the gel alternately with ethanol and deionized water is also included.

[0121] In one example, in step b2, before the step of sintering, the step further includes:

[0122] The step of drying the gel. It is understandable that the present application does not limit the equipment used for drying the gel. Preferably, the gel is dried using an infrared rapid dryer. In the infrared rapid dryer, the moisture in the gel can be quickly removed to solidify the gel, thereby avoiding the destruction of the gel structure that may be caused by long-term drying.

[0123] In one example, in step b2, the process parameters of the sintering treatment include: a sintering temperature of 400° C. to 600° C. In addition, in step b2, the process parameters of the sintering treatment also include: a sintering time of 0.5 h to 2 h.

[0124] Illustratively, the sintering temperature includes but is not limited to 400°C, 450°C, 500°C, 530°C, 540°C, 550°C, 560°C, 570°C or 600°C, or a range between any two of the above values.

[0125] Sintering under the above process parameters can convert the tin compounds in the gel into tin dioxide particles. Controlling the sintering temperature and time can adjust the size, shape and crystallinity of the tin dioxide particles, making them effectively suitable for compounding with tungsten disulfide nanosheets and improving the NO 2 sensitivity.

[0126] In one specific example, the steps of preparing the tin dioxide particles include:

[0127] (1) Dispersing a tin source in a second dispersant, adding a pH adjuster to adjust the pH to 3-3.5, and preparing a gel-containing dispersion; wherein the mass volume ratio of the tin source to the second dispersant is (2-5) g: (5-20) mL.

[0128] (2) Collecting the gel in the gel-containing dispersion, washing the gel at 50°C to 70°C in a water bath, washing the gel alternately with ethanol and deionized water, drying, heating the gel to 400°C to 600°C at a heating rate of 5°C / min to 10°C / min, sintering the gel, and keeping the temperature for 0.5h to 2h to prepare the tin dioxide particles.

[0129] The third aspect of the present application provides a nitrogen dioxide gas sensor, comprising a substrate, interdigitated electrodes and a gas sensitive layer, wherein the interdigitated electrodes are arranged on at least one side surface of the substrate, the gas sensitive layer is arranged on a side surface of the interdigitated electrodes away from the substrate, and the gas sensitive layer comprises the composite gas sensitive material described in any example of the first aspect of the present application.

[0130] The nitrogen dioxide gas sensor provided in this application is sensitive to NO 2 The detection limit of NO is low and can be achieved at room temperature. 2 Good response to NO 2 Has excellent selectivity.

[0131] In one example, the substrate includes one or more of a silicon substrate, a polymer substrate, a ceramic substrate, and a sapphire substrate.

[0132] In one example, the spacing between the positive electrode and the negative electrode of the interdigital electrodes is 100 μm to 900 μm, and the spacing between two adjacent interdigital electrodes is 50 μm to 500 μm.

[0133] Appropriate electrode spacing can optimize the electric field distribution and make the measured NO 2 The gas reacts more fully between the electrodes. 2 When gas molecules enter the area between the electrodes, the specific spacing ensures that the gas is fully in contact with the electrode surface, thereby improving the sensor's response to the gas and enhancing its sensitivity. In addition, different gases have different reaction characteristics at different electrode spacings. By adjusting the spacing between the interdigitated electrodes, the sensor can be made more sensitive to the target NO 2 Gas has higher selectivity. For example, the spacing between the positive electrode and the negative electrode of the interdigitated electrode includes but is not limited to 100μm, 200μm, 300μm, 400μm, 500μm, 600μm, 700μm, 800μm, or 900μm, or within the range of any of the above point values. For example, the spacing between two adjacent interdigitated electrodes includes but is not limited to 50μm, 100μm, 200μm, 300μm, 400μm, or 500μm, or within the range of any of the above point values.

[0134] In one example, the material of the interdigital electrodes is gold.

[0135] In a fourth aspect of the present application, a method for preparing the nitrogen dioxide gas sensor according to the third aspect of the present application is provided, comprising the following steps:

[0136] The interdigital electrodes are arranged on at least one side surface of the substrate;

[0137] The composite gas-sensitive material is made into a gas-sensitive layer coating liquid; the gas-sensitive layer coating liquid is coated on the surface of the interdigital electrode on one side away from the substrate, and after drying, the gas-sensitive layer is prepared.

[0138] Wherein, in the gas-sensitive layer coating liquid, the mass volume concentration of the composite gas-sensitive material is 1 mg / L~10 mg / L.

[0139] For example, in the gas-sensitive layer coating liquid, the mass volume concentration of the composite gas-sensitive material includes but is not limited to 1 mg / L, 2 mg / L, 3 mg / L, 4 mg / L, 5 mg / L, 6 mg / L, 7 mg / L, 8 mg / L, 9 mg / L, or 10 mg / L, or within the range of any of the above point values.

[0140] The following are specific examples. Unless otherwise specified, the raw materials used in the examples are all commercially available products.

[0141] Example 1

[0142] Embodiment 1 of the present application provides a nitrogen dioxide gas sensor and a preparation method thereof, comprising the following steps:

[0143] Preparation of tungsten disulfide nanosheets: (1) Place 500 mg of tungsten disulfide crystals (purchased from Beijing Inokai Technology Co., Ltd.) in a mortar and grind for 2 hours with the aid of acetonitrile (grinding medium), then place in a vacuum oven at 60°C and dry for 12 hours to remove excess acetonitrile to prepare an intermediate powder. (2) The intermediate powder is ultrasonically crushed at 400W for 2 hours in 300 mL of ethanol / water mixed solvent (35 vol%), and then subjected to a first centrifugal treatment at 2000 rpm for 30 minutes after ultrasonic treatment, and the supernatant is collected to prepare a tungsten disulfide nanosheet solution. (3) The tungsten disulfide nanosheet solution is subjected to a second centrifugal treatment at 8000 rpm for 30 minutes, the solid phase is collected, and then dried at 60°C for 12 hours to prepare the tungsten disulfide nanosheet.

[0144] The steps for preparing tin dioxide particles include: (1) dissolving 3.5 g of tin tetrachloride pentahydrate (purchased from: Sinopharm Chemical Reagent Co., Ltd.) in 8 mL of deionized water, and slowly dropping concentrated ammonia water and dilute ammonia water into the solution while stirring until the pH is adjusted to 3-3.5, to prepare a gel-containing dispersion. (2) collecting the gel in the gel-containing dispersion, washing the gel at 60° C. under a water bath condition, and washing the gel alternately with ethanol and deionized water. After washing, placing the white gel in an infrared rapid dryer for rapid drying, and after drying, placing the dried product in a muffle furnace, and sintering it at 550° C. for 30 minutes to prepare the tin dioxide particles.

[0145] Preparation of composite gas-sensitive material: (1) 20 mg of the prepared tungsten disulfide nanosheets were ultrasonically dispersed in 10 mL of ethanol / water mixed solvent (35 vol%) for 30 min to prepare a tungsten disulfide dispersion. (2) 1.22 mg of the prepared tin dioxide particles were ultrasonically dispersed in 2 mL of anhydrous ethanol for 30 min to prepare a tin dioxide dispersion. (3) Under stirring conditions, the tin dioxide dispersion was slowly dripped into the tungsten disulfide dispersion, and the mixed solution was ultrasonically treated for 4 h, so that at least part of the tin dioxide particles were loaded on the surface of the tungsten disulfide nanosheets to prepare an intermediate dispersion. (4) The intermediate dispersion was subjected to solid-liquid separation, and the solid was collected. After multiple centrifugal washings with water and ethanol, it was vacuum dried at 60°C for 12 h to prepare the composite gas-sensitive material. At this time, in the prepared composite gas-sensitive material, the molar ratio of the tungsten disulfide nanosheets to the tin dioxide particles is 1:0.1; the mass ratio of the tungsten disulfide nanosheets to the tin dioxide particles is 1:0.061.

[0146] Preparation of nitrogen dioxide gas sensor: (1) Add the prepared composite gas-sensitive material to deionized water at a concentration of 1 mg / L, and ultrasonicate it at 40 kHz for 10 minutes to make the composite material evenly dispersed in the deionized water to prepare the gas-sensitive layer coating liquid. (2) Prepare gold electrodes by micromachining technology, control the spacing between the positive and negative electrodes to 800 μm, and the spacing between adjacent electrodes to 300 μm. Take 1 μL of the gas-sensitive layer coating liquid and drop it on the electrode surface, and vacuum dry it at 60°C for 1 hour to obtain a nitrogen dioxide gas sensor.

[0147] Example 2

[0148] The preparation steps of Example 2 are basically the same as those of Example 1, with the main difference being that in the composite gas-sensitive material prepared in Example 2, the molar ratio of the tungsten disulfide nanosheets to the tin dioxide particles is 1:0.3; and the mass ratio of the tungsten disulfide nanosheets to the tin dioxide particles is 1:0.183.

[0149] Example 3

[0150] The preparation steps of Example 3 are basically the same as those of Example 1, with the main difference being that in the composite gas-sensitive material prepared in Example 3, the molar ratio of the tungsten disulfide nanosheets to the tin dioxide particles is 1:0.5, and the mass ratio of the tungsten disulfide nanosheets to the tin dioxide particles is 1:0.305.

[0151] Example 4

[0152] The preparation steps of Example 4 are basically the same as those of Example 1, with the main difference being that in the composite gas-sensitive material prepared in Example 4, the molar ratio of the tungsten disulfide nanosheets to the tin dioxide particles is 1:1. The mass ratio of the tungsten disulfide nanosheets to the tin dioxide particles is 1:0.61.

[0153] Comparative Example 1

[0154] Comparative Example 1 is basically the same as Example 1, except that the gas-sensitive material used in the gas sensor of Comparative Example 1 is only tungsten disulfide nanosheets. The specific preparation steps are as follows:

[0155] Preparation of tungsten disulfide nanosheets: (1) Place 500 mg of tungsten disulfide crystals (purchased from Beijing Inokai Technology Co., Ltd.) in a mortar and grind for 2 hours with the aid of acetonitrile (grinding medium), then place in a vacuum oven at 60°C and dry for 12 hours to remove excess acetonitrile to prepare an intermediate powder. (2) The intermediate powder is ultrasonically crushed at 400W for 2 hours in 300 mL of ethanol / water mixed solvent (35 vol%), and then subjected to a first centrifugal treatment at 2000 rpm for 30 minutes after ultrasonic treatment, and the supernatant is collected to prepare a tungsten disulfide nanosheet solution. (3) The tungsten disulfide nanosheet solution is subjected to a second centrifugal treatment at 8000 rpm for 30 minutes, the solid phase is collected, and then dried at 60°C for 12 hours to prepare the tungsten disulfide nanosheet.

[0156] Preparation of nitrogen dioxide gas sensor: (1) Add the prepared tungsten disulfide nanosheets to deionized water at a concentration of 1 mg / L, and ultrasonicate at 40KHz for 10 minutes to make the tungsten disulfide nanosheets evenly dispersed in the deionized water to prepare the gas-sensitive layer coating liquid. (2) Prepare gold electrodes using micromachining technology, control the spacing between the positive and negative electrodes to 800μm, and the spacing between adjacent electrodes to 300μm. Take 1 μL of the gas-sensitive layer coating liquid and drop it on the electrode surface, and vacuum dry it at 60℃ for 1 hour to obtain a nitrogen dioxide gas sensor.

[0157] Comparative Example 2

[0158] Comparative Example 2 is basically the same as Example 1, except that nano-flower-shaped molybdenum disulfide is used in Comparative Example 2. The specific preparation steps include:

[0159] Preparation of nano-flower-shaped molybdenum disulfide: (1) In an ice-water bath, add 60 mL of 0.2 mmol ammonium molybdate and 0.3 mmol N-acetylcysteine ​​(NAC) to a beaker and dissolve in 60 mL ultrapure water. Stir vigorously in an ice-water bath to obtain a precursor solution. (2) Pour 0.3 mmol thiourea into the precursor solution, stir for 5 min, add 20 mg polyvinylpyrrolidone (PVP), stir for 1 h, and hydrothermally react at 180 ° C for 4 h in the reaction device to obtain the product. (3) The product is centrifuged at 10,000 rpm for 1 h, washed alternately with anhydrous ethanol and deionized water three times, and then redispersed in deionized water to obtain a dispersion of nano-flower-shaped molybdenum disulfide.

[0160] Preparation steps of tin dioxide particles: same as in Example 1.

[0161] Preparation of composite gas-sensitive material: (1) 1.22 mg of prepared tin dioxide particles were ultrasonically dispersed in 2 mL of anhydrous ethanol for 30 min to prepare a tin dioxide dispersion. (2) Under stirring conditions, the tin dioxide dispersion was slowly dripped into the prepared nanoflower spherical molybdenum disulfide dispersion, and the mixed solution was ultrasonically treated for 4 h to prepare an intermediate dispersion. (4) The intermediate dispersion was subjected to solid-liquid separation, and the solid was collected. After multiple centrifugal washing with water and ethanol, it was vacuum dried at 60°C for 12 h to prepare the composite gas-sensitive material. At this time, in the prepared composite gas-sensitive material, the molar ratio of the nanoflower spherical molybdenum disulfide to the tin dioxide particles was 1:0.1; the mass ratio of the nanoflower spherical molybdenum disulfide to the tin dioxide particles was 1:0.061.

[0162] Preparation of nitrogen dioxide gas sensitive sensor: same as Example 1.

[0163] The composite gas-sensitive material prepared in Example 2 was subjected to characterization tests. Figure 2 is a SEM image of the composite gas-sensitive material prepared in Example 2 (the molar ratio of tungsten disulfide nanosheets to tin dioxide particles is 1:0.3). Figure 2 It can be seen that some tin dioxide nanoparticles aggregate to form aggregates, and the aggregates are loaded on tungsten disulfide nanosheets, and the average size of the tungsten disulfide nanosheets is 100nm to 300nm. Figure 3 This is the TEM image of the composite gas-sensitive material prepared in Example 2.

[0164] Depend on Figure 3 The observed lattice fringe spacing of 0.27 nm corresponds to WS 2The observed lattice fringe spacing of 0.34 nm corresponds to the SnO 2 Nanoparticles, which corresponds to SnO 2 In addition, a certain degree of lattice distortion can be observed at the interface between the two, which further confirms the generation of heterostructures.

[0165] Figure 4 The following are the XRD patterns of the tungsten disulfide nanosheets and composite gas-sensitive materials prepared in Example 2, as well as the XRD standard cards of tin dioxide and tungsten disulfide. Figure 4 It can be seen that the diffraction peaks of the tungsten disulfide nanosheets completely match the diffraction peaks of the XRD standard card of tungsten disulfide, and there are no other obvious impurity peaks in the XRD spectrum, which proves that the tungsten disulfide nanosheets obtained by peeling have high crystallinity and high crystal phase purity. In the XRD spectrum of the composite gas-sensitive material prepared in Example 2, its characteristic diffraction peaks correspond to the XRD standard cards of tin dioxide and tungsten disulfide, which indicates that the tin dioxide-tungsten disulfide composite material has been successfully formed.

[0166] The gas sensors prepared in the above-mentioned embodiments and comparative examples were tested.

[0167] The gas performance test is completed through the gas-sensitive performance test platform. The test platform is usually composed of a gas circuit control module, a signal acquisition module and a PC. By controlling the flow controller parameters corresponding to the background gas and the test gas of the gas circuit control module respectively, different concentrations of test gas can be obtained. When testing, connect the sensitive sensor to the signal acquisition module to start the test.

[0168] After the resistance value of the test gas sensor at the test temperature (25°C) is stabilized, NO 2 The concentration is 10ppm, and the ventilation time is uniformly controlled at 100 s to perform corresponding performance tests. In this application, unless otherwise specified, the response test refers to the test of the change of the resistance value Rg of the sensor in the test atmosphere and the resistance value Ra in the air environment, with Ra / Rg as the response value of the sensor; the response time refers to the time taken for the resistance value of the sensor to change to 90% of |Ra-Rg|, calculated from the time when the atmosphere in which the sensor is located changes from the air atmosphere to the test atmosphere.

[0169] The corresponding gas sensing response results of the gas sensors prepared in Examples 1 to 4 and Comparative Examples 1 to 2 are shown in Table 1.

[0170] Table 1

[0171]

[0172] As can be seen from Table 1, the gas sensors provided in Examples 1 to 4 of the present application are sensitive to NO 2 The response values ​​of are better than those of Comparative Examples 1 and 2. In Examples 1 to 4, as SnO 2 With the increase of SnO content, the response value shows a trend of increasing first and then decreasing, and the maximum value of 17.4 is obtained in Example 2. This is because when SnO 2 When the content is too high, SnO 2 Nanoparticles tend to aggregate together, reducing the adsorption sites for gas molecules and thus reducing the response value.

[0173] Figure 5 The gas sensors prepared in Examples 1 to 4 of the present application reacted to NO with a concentration of 10 ppm at room temperature. 2 Response curve diagram of Figure 6 The gas sensor prepared in Comparative Example 2 of the present application is sensitive to NO at a concentration of 10 ppm at room temperature. 2 The response curve of Figure 5 and Figure 6 It can be seen from the comparison that the gas sensors prepared in Examples 1 to 4 of the present application are sensitive to NO at a concentration of 10 ppm at room temperature. 2 The comparative example 2 uses nano-flower-shaped molybdenum disulfide as a carrier and composites it with tin dioxide particles. The response value is low and the recovery is difficult.

[0174] Figure 7 The following is a continuous response curve of the gas sensor of Example 2 to 1ppm, 2.5ppm, 5ppm, 10ppm, 25ppm, 50ppm and 100ppm of nitrogen dioxide at room temperature. In order to improve the experimental efficiency during the gas test, the ventilation time was controlled at 20s. Figure 6 It can be seen that as the gas concentration increases, the response value of the gas sensor of Example 2 also increases, and its minimum response concentration can reach 1 ppm.

[0175] Figure 8 The gas sensor of Example 2 is subjected to 10 ppm NO at room temperature every 3 days. 2 The response value of a test. Figure 8 It can be seen that as time goes by, the gas sensor of Example 2 is 2 The response value is basically maintained at around 17.4, indicating that it has relatively reliable long-term stability.

[0176] Fig. 9 The gas sensor of Example 2 was exposed to 10 ppm NO 2 , CO 2 NH3 , H 2 S and H 2 The response value in . Fig. 9 It can be seen that the gas sensor of Example 2 is effective for 10 ppm NO 2 The response value of NO is much higher than that of other gases with the same concentration, which shows that it has excellent NO 2 Selective.

[0177] The technical features of the above embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0178] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the content of the attached claims, and the description can be used to interpret the content of the claims.

Claims

1. A composite gas-sensitive material, characterized in that: The chemical components of the composite gas-sensitive material include tungsten disulfide and tin dioxide in a mass ratio of 1: (0.06-0.65), The tungsten disulfide includes tungsten disulfide nanosheets, the tin dioxide includes tin dioxide particles, and at least part of the tin dioxide particles are loaded on the surface of the tungsten disulfide nanosheets.

2. The composite gas-sensitive material according to claim 1, characterized in that: The composite gas-sensitive material has one or more of the following characteristics: (1) The average size of the tungsten disulfide nanosheets is 100nm~300nm; (2) The molar ratio of the tungsten disulfide to the tin dioxide is 1:(0.1~1).

3. A method for preparing the composite gas-sensitive material according to claim 1 or 2, characterized in that: The following steps are involved: Dispersing the tungsten disulfide nanosheets in a first solvent to prepare a tungsten disulfide dispersion; Dispersing the tin dioxide particles in a second solvent to prepare a tin dioxide dispersion; Under stirring conditions, the tin dioxide dispersion is added to the tungsten disulfide dispersion in batches, and after mixing, at least a portion of the tin dioxide particles are loaded on the surface of the tungsten disulfide nanosheets to prepare an intermediate dispersion; The intermediate dispersion is subjected to solid-liquid separation, and the solid is collected to prepare the composite gas-sensitive material.

4. The method for preparing a composite gas-sensitive material according to claim 3, characterized in that: The preparation method has one or more of the following characteristics: (1) In the tungsten disulfide dispersion, the mass volume concentration of the tungsten disulfide nanosheets is 1 mg / mL to 3 mg / mL; (2) In the tin dioxide dispersion, the mass volume concentration of the tin dioxide particles is 0.5 mg / mL to 5 mg / mL; (3) The molar ratio of the tungsten disulfide nanosheets to the tin dioxide particles in the intermediate dispersion is 1: (0.1-1); (4) the first solvent includes one or more of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone; (5) The second solvent includes one or more of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone.

5. The method for preparing a composite gas-sensitive material according to claim 3 or 4, characterized in that: The preparation steps of the tungsten disulfide nanosheets include: Grinding the tungsten disulfide crystals in the presence of grinding media, and preparing an intermediate powder after drying; Ultrasonic dispersion of the intermediate powder in a first dispersant, performing a first centrifugal treatment, collecting the supernatant, and preparing a tungsten disulfide nanosheet solution; The tungsten disulfide nanosheet solution is subjected to a second centrifugal treatment to collect the solid phase to prepare the tungsten disulfide nanosheet; Wherein, the process parameters of the first centrifugal treatment include: a rotation speed of 1000 rpm to 3000 rpm; The process parameters of the second centrifugal treatment include: a rotation speed of 7000 rpm to 9000 rpm.

6. The method for preparing the composite gas-sensitive material according to claim 5, characterized in that: The preparation steps of the tungsten disulfide nanosheets have one or more of the following characteristics: (1) The grinding medium includes one or more of acetonitrile, isopropanol and N-methylpyrrolidone; (2) the first dispersant includes one or more of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone; (3) In the step of ultrasonically dispersing the intermediate powder in the first dispersant, the mass volume ratio of the intermediate powder to the first dispersant is (400-600) mg: (200-400) mL; (4) In the step of ultrasonically dispersing the intermediate powder in the first dispersant, the process parameters of the ultrasonic dispersion include: ultrasonic crushing at a power of 300W to 600W.

7. The method for preparing a composite gas-sensitive material according to claim 3 or 4, characterized in that: The steps of preparing the tin dioxide particles include: Dispersing the tin source in the second dispersant, adding a pH adjuster to adjust the pH to 3-3.5, and preparing a gel-containing dispersion; The gel in the gel-containing dispersion is collected, dried, and then sintered to prepare the tin dioxide particles.

8. The method for preparing a composite gas-sensitive material according to claim 7, characterized in that: The steps for preparing the tin dioxide particles have one or more of the following characteristics: (1) The tin source includes tin tetrachloride pentahydrate; (2) the second dispersant includes one or more of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone; (3) The pH adjuster includes one or more of ammonia water, sodium hydroxide solution and potassium hydroxide solution; (4) in the step of dispersing the tin source in the second dispersant, the mass volume ratio of the tin source to the second dispersant is (2-5) g: (5-20) mL; (5) The process parameters of the sintering treatment include: the sintering temperature is 400℃~600℃.

9. A nitrogen dioxide gas sensor, characterized in that: It comprises a substrate, interdigitated electrodes and a gas-sensitive layer, wherein the interdigitated electrodes are arranged on at least one side surface of the substrate, the gas-sensitive layer is arranged on a side surface of the interdigitated electrodes away from the substrate, and the gas-sensitive layer comprises the composite gas-sensitive material according to claim 1 or 2, wherein the material of the interdigitated electrodes is gold.

10. A method for preparing a nitrogen dioxide gas sensor according to claim 9, characterized in that: The following steps are involved: The interdigital electrodes are arranged on at least one side surface of the substrate; The composite gas-sensitive material is made into a gas-sensitive layer coating liquid; the gas-sensitive layer coating liquid is coated on the surface of the interdigital electrode on the side away from the substrate, and after drying, the gas-sensitive layer of the nitrogen dioxide gas sensor is prepared.